Biochemical and proteomic analyses of venom from a new pit viper, Protobothrops kelomohy - Chanhome,Lawan (2022)
Abstract Background: A new pit viper, Protobothrops kelomohy, has been recently discovered in northern and northwestern Thailand. Envenoming by the other Protobothrops species across several Asian countries has been a serious health problem since their venom is highly hematotoxic. However, the management of P. kelomohy bites is required as no specific antivenom is available. This study aimed to investigate the biochemical properties and proteomes of P. kelomohy venom (PKV), including the cross-neutralization to its lethality with antivenoms available in Thailand. Methods: PKV was evaluated for its neutralizing capacity (ER50), lethality (LD50), procoagulant and hemorrhagic effects with three monovalent antivenoms (TAAV, DSAV, and CRAV) and one polyvalent (HPAV) hematotoxic antivenom. The enzymatic activities were examined in comparison with venoms of Trimeresurus albolabris (TAV), Daboia siamensis (DSV), Calloselasma rhodostoma (CRV). Molecular mass was separated on SDS-PAGE, then the specific proteins were determined by western blotting. The venom protein classification was analyzed using mass spectrometry-based proteomics. Results: Intravenous LD50 of PKV was 0.67 µg/g. ER50 of HPAV, DSAV and TAAV neutralize PKV at 1.02, 0.36 and 0.12 mg/mL, respectively. PKV exhibited procoagulant effect with a minimal coagulation dose of 12.5 ± 0.016 µg/mL and hemorrhagic effect with a minimal hemorrhagic dose of 1.20 ± 0.71 µg/mouse. HPAV was significantly effective in neutralizing procoagulant and hemorrhagic effects of PKV than those of TAAV, DSAV and CRAV. All enzymatic activities among four venoms exhibited significant differences. PKV proteome revealed eleven classes of putative snake venom proteins, predominantly metalloproteinase (40.85%), serine protease (29.93%), and phospholipase A2 (15.49%). Conclusions: Enzymatic activities of PKV are similarly related to other viperid venoms in this study by quantitatively hematotoxic properties. Three major venom toxins were responsible for coagulopathy in PKV envenomation. The antivenom HPAV was considered effective in neutralizing the lethality, procoagulant and hemorrhagic effects of PKV.